Szerb etnoregionalista törekvések 1848-1849 - Gulyás, László (Közép-Európai Közlemények, 2012)
In the title of our study we use the expression „ethnoregionalist” that we define as follows. We can talk about ethnoregionalism, if a region formed by economic and social processes is more or less the same as the territory formed by language and/or religion. In the 19th century, in the Carpathian Basin not only Hungarians, but other nationalities (Croats, Romanians, Slovaks and Serbs) claimed their own territory in the frame of historical Hungarian Kingdom. Practically it meant that they expressed etnoregionalist objectives against the Hungarian Kingdom. In our study we present the etnoregionalist efforts of the Serbs living in Hungary in 1848–49, and the response of the dominant Hungarian nation to these efforts.